Lessons from four case studies using games for social learning in India - Falk, Thomas; Zhang, Wei; Meinzen-Dick, Ruth S.; Bartels, Lara (2021)
By Thomas Falk, Wei Zhang, Ruth Meinzen-Dick, and Lara Bartels